Revision of the spider genus Hamataliwa Keyserling from China (Araneae: Oxyopidae) - Zhang, Jun-Xia; Zhu, Ming-Sheng; Song, Da-Xiang (Zootaxa, 2005)
Five lynx spider species of the genus Hamataliwa Keyserling from China are described, including two new species, Hamataliwa aurita sp. nov. and H. cordata sp. nov. The species Oxyopes labialis Song, 1991 and O. sikkimensis Tikader, 1970 are transferred to Hamataliwa as their genital structures are coherent with the diagnosis of Hamataliwa. The species H. sanmenensis Song & Zheng, 1992 is redescribed from type specimens from Sanmen County of Zhejiang Province, China. A key to Chinese species of Hamataliwa is provided.